2015
DOI: 10.1007/s10459-015-9631-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender, religion, and sociopolitical issues in cross-cultural online education

Abstract: Cross-cultural education is thought to develop critical consciousness of how unequal distributions of power and privilege affect people's health. Learners in different sociopolitical settings can join together in developing critical consciousness -awareness of power and privilege dynamics in society -by means of communication technology. The aim of this research was to define strengths and limitations of existing cross-cultural discussions in generating critical consciousness. The setting was the FAIMER intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A variety of factors might impact or influence the learning outcomes of the mentees during the online mentorship, such as gender, religion and socio‐political issues (Zaidi, Verstegen, Naqvi, Morahan, et al, 2016). Amongst these factors, a healthy mentor–mentee association or relationship would be one of the essential factors for achieving optimal learning (Chan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of factors might impact or influence the learning outcomes of the mentees during the online mentorship, such as gender, religion and socio‐political issues (Zaidi, Verstegen, Naqvi, Morahan, et al, 2016). Amongst these factors, a healthy mentor–mentee association or relationship would be one of the essential factors for achieving optimal learning (Chan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is also needed to determine whether an intervention such as Identity Text increases dialogue on sociocultural issues in a professional development setting (15). …”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research emphasizes this challenge. We found that health professions educators from diverse cultures who were participating in residential program sessions, followed by online distance educational discussions, made surprisingly few references to sociopolitical events or norms in their home countries (15). When they did, their online contributions were more likely to be greeted by silence or superficial, short-lived discussions than in-depth exploration of the issues raised.…”
mentioning
confidence: 99%
“…The listserv is used for formal e-learning modules, alumni-designed community conversations, and as an informal resource network and a social support network for Fellows. During the formal e-learning sessions, Fellows are required to post ‘at least one substantive comment that advances the topic’, but are not given any specific guidelines to deliberately post comments to promote multicultural discourse (18). …”
Section: Methodsmentioning
confidence: 99%
“…We have operationally defined ‘educational cultural hegemony’ as educational practices where teachers assume that the content and task is ‘culture free’ and, therefore, implicitly discourage bringing in personal cultural context. We found that health professions educators from over 40 countries rarely mentioned culture; they focused rather on the specific educational content and tasks (18). As a follow-up to the study, here we aim to explore educational cultural hegemony further by analyzing participant responses to a direct call to discuss cultural issues.…”
mentioning
confidence: 99%